The effect of innovation and strategic resources on capital structure - Faria, Aline Mariane de (2024)
Innovation is crucial for competitive companies. To effectively implement innovation, it is necessary to have substantial financial resources. Traditionally, financing sources such as venture capital and angel investors are considered more suitable. In contrast, debt is considered less suitable due to the risky nature of innovation, which creates a negative association between innovation and debt. At the same time, the resource-based view emphasizes the importance of resources for successfully executing strategies. Therefore, we aim to identify the effect of the interaction of innovation strategy and strategic resources on companies’ debt (capital structure). This finding is relevant since, despite the literature indicating that debt is inappropriate for innovation, it remains one of the most common sources of financing an innovative project. We show that a firm with an innovation strategy and strategic resources has greater financial leverage. The sample included American companies, covering 3,628 companies from 2008 to 2018.